Descriptive analysis of the annual cost of treating spasticity with different types of botulinum toxin A - D. Hernández Herrero; J.C. Miangolarra Page (Neurología (English Edition), 2022)
Introduction: Botulinum toxin A is the first-line treatment for localised spasticity. However, the economic impact of this treatment is not fully known. This study aimed to describe the real costs of botulinum toxin A for the treatment of adult patients with spasticity at a spasticity clinic pertaining to a rehabilitation service, over a period of one year. Methods: We retrospectively reviewed all medical procedures carried out during the year 2017. We collected data on the type of toxin used (incobotulinumtoxin A, onabotulinumtoxin A, or Abobotulinumtoxin A), the number of units injected, the anatomical region, and the time elapsed between infiltrations. The costs of medication and indirect costs, such as staff and consumables, were also calculated. Results: This is the first study to describe the real costs of botulinum toxin treatment of spasticity in adult patients in Spain. In 2017, 510 infiltration procedures were performed in 164 patients. The total cost of treating spasticity in our service was 116 789.70. The mean annual cost per patient was 603.64 for onabotulinumtoxin A, 642.69 for abobotulinumtoxin A, and 707.59 for incobotulinumtoxin A. Conclusions: Our economic study of real clinical practice is consistent with the theoretical models published in the literature. The different characteristics of each toxin and the inability to establish an equivalence between the units of each drug prevents us from directly comparing these costs. Resumen: Introducción: La toxina botulínica A es el tratamiento de elección para la espasticidad localizada. Sin embargo, no se tiene un conocimiento real de su repercusión económica. El objetivo de este trabajo es describir los costes reales del tratamiento de la espasticidad en adultos con toxina botulínica A en una consulta de espasticidad de un Servicio de Rehabilitación, a lo largo de un año. Métodos: Se ha realizado la revisión retrospectiva de todos los actos médicos llevados a cabo a lo largo del año 2017. Se han recogido el tipo de toxina utilizado (incobotulinumtoxin A, onabotulinumtoxin A, abobotulinumtoxin A), las unidades inyectadas, la región anatómica y el tiempo transcurrido entre infiltraciones. Se han obtenido los costes de la medicación y los costes indirectos, como los de personal o fungibles. Resultados: Este es el primer trabajo que describe los costes reales del tratamiento de la espasticidad en adultos con toxina botulínica A en España. En 2017 se realizaron 510 actos de infiltración en 164 pacientes. El coste total de tratamiento de espasticidad en nuestro Servicio fue de 116.789,70 . El coste medio anual por paciente fue 603,64 para onabotulinumtoxin A, 642,69 para AbotoxA y 707,59 para incobotulinumtoxin A. Conclusiones: Nuestro estudio económico de actividad clínica real sigue una pauta similar a la descrita en los modelos teóricos publicados en la literatura. Las diferentes características de cada toxina y la imposibilidad de establecer una equivalencia entre las unidades de cada una de ellas impiden la comparación directa de estos costes.